Between technocracy and politics: How financial stability committees shape precautionary interventions in real estate markets. Issue 2 (11th June 2022) - Thiemann, Matthias; Stellinga, Bart
Abstract: Implementing precautionary measures that have obvious distributional consequences today but often only invisible future benefits is politically difficult. It requires that policymakers reconcile technocratic expertise with political consent. This paper traces attempts to enact such measures, focusing on countercyclical policies to limit the systemic risks of housing booms as proposed by financial stability committees in Germany, France, and the Netherlands from 2015 onwards. These committees bring together technocrats and political authorities in order to overcome the inaction bias inherent to these measures, seeking to forge both epistemic and political consensus on the need for action. We find that the work of these committees is characterized by lengthy processes of consensus‐building, during which technocrats amass evidence and search for politically acceptable solutions. We argue that whether this leads to meaningful steps crucially depends on the committee's institutional set‐up. What particularly matters is its capacity to engage the Ministry of Finance in binding discussions and the governance arrangements for the activation of precautionary instruments, which shape whether a shared framing of the problem and appropriate response emerges.